A Chemical Tool for In Vitro and In Vivo Precipitation of Lysine Methyltransferase G9a. Issue 3 (17th January 2014) - Konze, Kyle D.; Pattenden, Samantha G.; Liu, Feng; Barsyte‐Lovejoy, Dalia; Li, Fengling; Simon, Jeremy M.; Davis, Ian J.; Vedadi, Masoud; Jin, Jian
Abstract Here we report the design, synthesis, and biochemical characterization of a new chemical tool, UNC0965. UNC0965 is a biotinylated version of our previously reported G9a chemical probe, UNC0638. Importantly, UNC0965 maintains high in vitro potency and is cell penetrant. The biotinylated tag of UNC0965 enables "chemiprecipitation" of G9a from whole cell lysates. Further, the cell penetrance of UNC0965 allowed us to explore the localization of G9a on chromatin both in vitro and in vivo through chemical inhibitor‐based chromatin immunoprecipitation (chem‐ChIP).